The progress in the relationship between trace elements and acute lymphoblastic leukemia - Wang, Jing; Huang, Pei; Lang, Changhui; Luo, Yan; He, Zhixu; Chen, Yan (Frontiers in Cell and Developmental Biology, 2023)
Trace elements are very important substances with low content in the human body. If the content of some trace elements changes, they are also related to diseases. Acute lymphoblastic leukemia (ALL) is a malignant blood tumor, and its relationship with trace elements has also been a concern by scholars. Not only have the trace element levels in ALL patients changed, but the efficacy of different treatment methods has also been linked to the corresponding trace element changes. The characteristics of ALL may be related to the dysregulation of differentiation and proliferation of lymphoid precursor cells. Cell proliferation and differentiation are often affected by changes in DNA levels. However, trace elements are involved in DNA damage and repair mechanisms. In recent years, as an increasing number of studies believe that ALL is related to the abnormal metabolism of trace elements in the body, this paper intends to discuss the research progress on the relationship between trace elements and ALL to provide more information on trace elements for the diagnosis, treatment, and prevention of ALL.